2010
DOI: 10.3844/ajeassp.2010.133.137
|View full text |Cite
|
Sign up to set email alerts
|

Confined High Strength Concrete Columns: An Experimental Study

Abstract: Problem statement: An experimental study on GFRP confined high strength concrete columns has been carried out with a view to evaluate its performances under uni-axial compression in terms of load and deformation capacity. Approach: High strength concrete columns strengthened with different configuration and stiffness of GFRP wraps were tested under axial compression until failure. Their response evaluated at different load levels. Results: The test results clearly indicated GFRP wrapped hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Many experimental research results were reported in the area of compressive and tensile strength of concrete at different strain rates (Abu-Lebdeh et al, 2010;Ravichandran et al, 2009;Kotsovos, 1983). A selection of the commonly published results is also reported by Saravanan et al, 2010;Bischoff and Perry, 1991;and Malvar and Crawford (1998) as presented in Fig. 1 and and Fig.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Many experimental research results were reported in the area of compressive and tensile strength of concrete at different strain rates (Abu-Lebdeh et al, 2010;Ravichandran et al, 2009;Kotsovos, 1983). A selection of the commonly published results is also reported by Saravanan et al, 2010;Bischoff and Perry, 1991;and Malvar and Crawford (1998) as presented in Fig. 1 and and Fig.…”
Section: Introductionmentioning
confidence: 84%
“…The DIF of concrete can be as high as 4 in compression and up to 6 in tension for strain rates in the range of 102-103 sec −1 (Sezen and Moehle, 2006). Based on experimental and analytical data reported by different researchers (Bischoff and Perry, 1991;CEB-FIP, 1993;Ngo et al, 2007;Saravanan et al, 2010;Abu-Lebdeh et al, 2010) the proposed strength increase factor (k d or DIF) can be presented as indicated in Eq. 1 and 2 and shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The unconfined compressive strength of VHSC can be five times the compressive strength of the conventional normal concrete and toughness of about eight times greater than that of conventional fiber reinforced concrete. These superior properties were achieved by considering several factors such as low flaws, particle packing, improved material homogeneity, low water cement ratio, mixing method and special curing treatment (Abu-Lebdeh et al, 2010a;2010b;O'Neil et al, 1999;Hamoush et al, 2010;Ravichandran et al, 2009;Saravanan et al, 2010). To date, researchers continue working on enhancing the properties of this new concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed advanced cement-based materials like high strength concrete (HSC), ultra-high strength concrete (UHSC), or high performance (HPC) and ultrahigh performance (UHPC) concretes have shown drastic improvement in compressive strength, E-modulus, flexural strength as well as tensile strength (Richard 1994;Benjamin 2006;Saravanan 2010). However, one of the major disadvantages of these types of concretes is a low tensile strain capacity or ductility.…”
Section: Background and Strain Hardening Theory Of Shccmentioning
confidence: 99%